Pharmacological Activation of Nrf2 Pathway Improves Pancreatic Islet Isolation and Transplantation. Issue 11 (November 2015) - Li, Shiri; Vaziri, Nosratola D.; Masuda, Yuichi; Hajighasemi-Ossareh, Mohammad; Robles, Lourdes; Le, Aimee; Vo, Kelly; Chan, Jefferson Y.; Foster, Clarence E.; Stamos, Michael J.; Ichii, Hirohito
Oxidative stress is a major cause of islet damage and loss during the islet isolation process. The Nrf2 pathway plays a critical role in protecting the cells against oxidative stress. The aim of this study was to investigate the effect of an Nrf2 activator (dh404) on islet isolation and transplantation in a rodent model. Islet isolation was conducted using Nrf2-deficient and wild-type mice and vehicle-treated and Nrf2 activator (dh404)-treated rats. Islet yield, viability, and Nrf2 pathway activity were determined. An in vivo islet potency test was done. Islet yield and viability in Nrf2-deficient mice was significantly lower compared to wild-type ( p < 0.05) mice. Furthermore, administration of dh404 to normal Sprague–Dawley rats enhanced nuclear translocation of Nrf2 and elevated HO-1 expression in the pancreas. Islet yield and viability in dh404-treated rats was significantly higher compared to the vehicle-treated group ( p < 0.05). The diabetes cure rate in nude mice with chemically induced diabetes was significantly greater in those transplanted with islets from the dh404-treated group (6/9) than vehicle-treated rats (2/9, p < 0.05). The Nrf2 pathway plays a significant role in protecting islets against stress caused by the isolation process. Pharmacological activation of the Nrf2 pathway significantly increased HO-1 expression, improved islet yield, viability, and function after transplantation.